2004
DOI: 10.1023/b:bile.0000009464.23026.e0
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological production of l(+)-lactic acid from wood hydrolyzate by batch fermentation of Enterococcus faecalis

Abstract: The inhibition of lactic acid fermentation by wood hydrolyzate was decreased (approx. 20%) by adaptation of Enterococcus faecalis RKY1 to wood hydrolyzate-based medium whereby lactic acid productivity and cell growth were enhanced by 0.5 g l(-1) h(-1) and 2.1 g l(-1), respectively. When the diluted or concentrated wood hydrolyzate (equivalent to 25-100 g glucose l(-1)) was supplemented with 15 g yeast extract l(-1), 24-93 g lactic acid l(-1) was produced at a rate between 1.7 g l(-1) h(-1) and 3.2 g l(-1) h(-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 9 publications
0
63
0
3
Order By: Relevance
“…Lactic acid has many applications as a food additive, acidulant, as well in the production of biodegradable polylactic acid [81,82]. Food-grade lactic acid has a price ranging between $1.38 per kilogram (50% purity) and $1.88 per kilogram (88% purity) [83,84]. Compared to traditional chemical synthesis methods, microbial conversion of lactic acid favors the formation of one specific configuration, either D-or L-, due to the high specificity of lactate dehydrogenase (LDH) [28,29], a property that can simplify downstream processes such as separation and purification.…”
Section: Escherichia Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactic acid has many applications as a food additive, acidulant, as well in the production of biodegradable polylactic acid [81,82]. Food-grade lactic acid has a price ranging between $1.38 per kilogram (50% purity) and $1.88 per kilogram (88% purity) [83,84]. Compared to traditional chemical synthesis methods, microbial conversion of lactic acid favors the formation of one specific configuration, either D-or L-, due to the high specificity of lactate dehydrogenase (LDH) [28,29], a property that can simplify downstream processes such as separation and purification.…”
Section: Escherichia Speciesmentioning
confidence: 99%
“…The yield of hydrogen and ethanol were 0.74 and 0.92 mol/mol glycerol respectively. The consumption of glycerol can be increased from 45.7% to 84.5% through the application of a potential of 0.2 V. Mixed culture MECs with a single chamber design can produce hydrogen yields of 3.9 mol/mol and 5.4 mol/mol glycerol, higher than pure culture MECs, with applied voltages of 0.9 and 1.0 V [79,80]. The application of pretreatments like heat shock should be considered to before inoculation as a method to prevent growth of methanogens.…”
Section: Microbial Electrochemical Conversionmentioning
confidence: 99%
“…Wood is currently considered as a fairly attractive raw material for use in its production [10][11][12]. However, it has become necessary, in recent years, to develop an alternative nitrogen source which is cheaper than the yeast extract traditionally employed in the cultivation of lactic acid bacteria, because production costs are highly dependent on the nitrogen source cost, as well as the carbon source cost [13].…”
Section: Introductionmentioning
confidence: 99%
“…26 Few studies have reported the dilute-acid hydrolysis of lignocellulosic biomass from wood and the use of microorganism with ability to produce lactic acid in these hydrolysates. 18,[27][28][29] Optimization of hydrolysis conditions is necessary for improving the efficiency of biomass conversion processes. Rafiqul et al 30 pointed out that xylose release via acid bioconversion of Meranti wood sawdust depended on a number of process factors like temperature, H 2 SO 4 concentration, and residence time.…”
Section: Introductionmentioning
confidence: 99%